2013
DOI: 10.1002/hed.23437
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy accelerates vascularization in keratinized oral mucosal surgical flaps

Abstract: Our results suggest that HBOT is capable of advancing wound vascular regeneration in healing keratinized oral mucosal flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…9 Subsequently, more oxygenated blood can reach the wound, thereby maintaining the integrity of the healed tissue after the therapy sessions. 8,13 Bayati el al 14 reported a marked increase in the area of myocutaneous flap survival through improved vascularity using hyperbaric oxygen. Perrins 15 conducted a randomized controlled trial and found an overall 29% improvement in skin graft survival in the group treated with hyperbaric oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Subsequently, more oxygenated blood can reach the wound, thereby maintaining the integrity of the healed tissue after the therapy sessions. 8,13 Bayati el al 14 reported a marked increase in the area of myocutaneous flap survival through improved vascularity using hyperbaric oxygen. Perrins 15 conducted a randomized controlled trial and found an overall 29% improvement in skin graft survival in the group treated with hyperbaric oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…The intermittent application stimulates new vascularization in the affected tissue, as observed in oral mucosal flaps in rabbits. 8 Also, by increasing oxygen levels, white blood cell counts and fibroblast function improve. 9 Through these mechanisms, HBOT could be beneficial in nonirradiated patients with intraoral compromised wound healing.…”
mentioning
confidence: 99%
“…Zamboni et al found using in vitro and in vivo animal studies that ischemiareperfusion injury was minimized through a nitric oxide mediated mechanism that resulted in decreased polarization of the CD18 on neutrophils (Zamboni2). Additionally, several animal studies have shown the benefit of HBOT in neovascularization of ischemic tissue flaps (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a plethora of information on the biological effects of placing humans in hyperbaric oxygen (100% O 2 environment at 2.4–3.0 atm) for single or multiple 2 h treatments, with or without irradiation (3739). Among the known benefits of hyperbaric oxygen therapy are: 1. improved tumor response to radiation therapy (37, 40, 41); 2. stimulation of cell renewal (42, 43); 3. increased growth of new blood vessels (4346); 4. decreased inflammation (46, 47); 5. increased ability to fight infection (48); and 6. stimulation of collagen production (39, 49, 50). With the possible exception of decreased neuroinflammation, none of these should positively affect radiation-induced cognitive impairment after breathing 100% O 2 for a single 2.5 h period.…”
Section: Discussionmentioning
confidence: 99%